Epidemiology of osteoporosis in postmenopausal women aged 47 to 60 years - Meiyanti, Meiyanti (Universa Medicina, 2010)
Osteoporosis is a disorder having the characteristic features of low bone mass and structural degeneration. There are several factors affecting the prevalence of osteoporosis in postmenopausal women, such as age, age at menarche, duration of menopause, dietary or nutritional intakes, life style and level formal education. In connection with the increasing global prevalence of osteoporotic fractures, the purpose of the present study was to determine the prevalence and the influencing factors of osteoporosis in postmenopausal women. A cross-sectional study, involving 203 postmenopausal women aged 47-60 years, was conducted in 4 villages of Mampang Prapatan subdistrict, from February to April 2010. Bone mineral density (BMD) of lumbar spine 1-4, femoral neck, and left radius was measured by dual-energy X-ray absorptiometry (Lunar DPX Bravo Nomusa densitometer, GE Medical Systems) at Budi Jaya Hospital, Jakarta. The T-score threshold, defined as Â£ -2.5 was used to identify subjects with osteoporosis The results of the study showed that the highest prevalence of osteopenia of 45.8% was found in the femoral neck, while the highest prevalence of osteoporosis of 30% was found in the distal radius. Age, duration of menopause, and number of pregnancies yielded a significant correlation with BMD of the lumbar vertebrae and the distal radius. Body mass index (BMI) was also significantly correlated with BMD of lumbar vertebrae, femoral neck and distal radius. Effective strategies for the prevention and management of osteopenia and osteoporosis are needed.